Modeling and analysis of power extraction circuits for passive UHF RFID applications - 樊勃 戴宇杰 张小兴 吕英杰 (Journal of semiconductors, 2009)
Modeling and analysis of far field power extraction circuits for passive UHF RF identification （RFID） applications are presented. A mathematical model is derived to predict the complex nonlinear performance of UHF voltage multiplier using Schottky diodes. To reduce the complexity of the proposed model, a simple linear approximation for Schottky diode is introduced. Measurement results show considerable agreement with the values calculated by the proposed model. With the derived model, optimization on stage number for voltage multiplier to achieve maximum power conversion efficiency is discussed. Furthermore, according to the Bode-Fano criterion and the proposed model, a limitation on maximum power up range for passive UHF RFID power extraction circuits is also studied.